Assessing the factor structure of acute stress disorder symptoms among Filipino adolescent survivors of a deadly flash flood disaster - Mordeno, Imelu G. (Animo Repository, 2016)
Acute Stress Disorder (ASD) was introduced in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) to account for stress symptoms appearing within the first month after a trauma exposure. However, there is scant literature assessing the validity of models pertaining to ASD, particularly among Asian adolescent samples. This study aims to address this gap by examining the latent structure of five proposed models of ASD among adolescent survivors of a deadly flash flood. Two hundred twenty-five (225) respondents were assessed using the Acute Stress Disorder Interview within a month after a flash flood disaster. Series of confirmatory factor analyses indicated that a five-factor inter-correlated model (dissociation, intrusion, avoidance, dysphoric arousal and anxious arousal) yielded a more nuanced structure that portrays the subtleties in the data that are glossed over and missed by one-factor DSM-5 and even other multifactor models. © 2015, Springer Science+Business Media Dordrecht.